2022
DOI: 10.17245/jdapm.2022.22.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic efficacy of supplemental intraligamentary injection in human mandibular teeth with irreversible pulpitis: a systematic review and meta-analysis

Abstract: Background Inferior alveolar nerve block (IANB) is known to have a lower success rate for anesthesia in patients with irreversible pulpitis. This calls for supplementary techniques to effectively anesthetize such patients. This systematic review aimed to evaluate the published literature for determining the success rate of anesthesia induction using post-IANB intraligamentary (IL) injection in the mandibular teeth of patients with symptomatic irreversible pulpitis. The review question was, “What i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…For dental treatments, supplemental injections such as intraligamentary anesthesia, intraosseous anesthesia and infiltration anesthesia are recommended. Supplemental intraligamentary injections following the failure of IANB have been shown to be effective ( Gupta et al., 2022 ). Computer-controlled anesthesia offers certain advantages compared to traditional anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…For dental treatments, supplemental injections such as intraligamentary anesthesia, intraosseous anesthesia and infiltration anesthesia are recommended. Supplemental intraligamentary injections following the failure of IANB have been shown to be effective ( Gupta et al., 2022 ). Computer-controlled anesthesia offers certain advantages compared to traditional anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the search for an efficient anesthetic technique/solution over the decades that will achieve efficient anesthesia. Additionally, in symptomatic irreversible pulpitis cases, IANB showed less than a 30% success rate of anesthesia [ 4 , 5 , 17 ] due to the inflammation-related activation of specific receptors such as tetrodotoxin-resistant receptors [ 35 ] directly resisting the concentration of local anesthetic agents and reducing their efficacy [ 33 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent randomized clinical trial that used 72 patients to assess the effectiveness and complications of intra-ligamentary anesthesia with IANB found both techniques to be equivalent in effectiveness for pain control, and at the same time, intra-ligamentary injections showed significantly less pain during injection [ 16 ]. A recent systematic review and meta-analysis that evaluated the success rate of supplementary IL injection in the mandibular teeth of patients with irreversible pulpitis also found that these injections provide better success rates for anesthesia and increased the efficacy of anesthesia [ 17 ]. It might be noted that there are few reports of ILA causing some damage to periodontal tissue, bone, and even cause root resorption if not used cautiously.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another randomized clinical trial demonstrated 100% and 56.3% success rates for supplemental IL injection of 4% articaine in mandibular second and first molars, respectively [ 22 ]. According to the pooled quantitative analyses of a recent systematic review, supplemental IL injections could increase the overall anesthetic success rate [ 30 ]. The higher success of IL injection in second molars may be attributable to the higher porosity of the cribriform plate surrounding the mandibular second molars; the greater the porosity, the greater the potential permeability [ 31 32 ].…”
Section: Discussionmentioning
confidence: 99%